2016
DOI: 10.1001/jamaophthalmol.2016.3513
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomographic Angiography in Acute Macular Neuroretinopathy

Abstract: In summary, our findings provide another example in which OCTA may further expand our understanding of retinal and choroidal pathophysiology. While the observations in these 3 eyes from 2 patients should not be interpreted as proving cause and effect, the results do suggest that CC flow abnormalities may be associated with the cause of AMN. Further studies would be needed to validate this observation. ARTICLE INFORMATION

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
39
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 16 publications
2
39
0
1
Order By: Relevance
“…They found that CC flow abnormalities colocalised with the OCT alterations of the AMN lesions and suggested a vascular insult in the CC as the pathogenic mechanism of the AMN lesions 5. In reply to the latter report, Ashraf et al 7 suggested caution in the interpretation of the latter findings by observing that the low void signal seen in the CC on OCT-A may represent a shadowing artefact resulting from the overlying retinal layers.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They found that CC flow abnormalities colocalised with the OCT alterations of the AMN lesions and suggested a vascular insult in the CC as the pathogenic mechanism of the AMN lesions 5. In reply to the latter report, Ashraf et al 7 suggested caution in the interpretation of the latter findings by observing that the low void signal seen in the CC on OCT-A may represent a shadowing artefact resulting from the overlying retinal layers.…”
Section: Discussionmentioning
confidence: 97%
“…Thanos et al 5 first reported the use of OCT-A in two patients with AMN. They found that CC flow abnormalities colocalised with the OCT alterations of the AMN lesions and suggested a vascular insult in the CC as the pathogenic mechanism of the AMN lesions 5.…”
Section: Discussionmentioning
confidence: 99%
“…AMN predominantly occurs in young healthy women, causes acute visual disturbance such as parafoveal scotoma and is characterized by Intraretinal, reddish-brown, wedgeshaped lesions on OCT that resemble retinal light damage [9]. Recently, it was reported that AMN is associated with circulatory disturbance in the Choriocapillaris [10]. In our case, the absence of a typical reddish-brown lesion around the fovea and the circulatory deficit in both retinal and Choroidal capillary layers rendered AMN unlikely.…”
Section: Discussionmentioning
confidence: 60%
“…[ 4 ] As such, AMN has been associated with conditions such as oral contraceptives, flu-like illness, and certain hypotensive states such as nocturnal hypotension. [ 5 8 ] The lesions of AMN are characteristic and typically localized to the outer retina due to ischemia of the DCP. Features of AMN include hyperreflectivity of the OPL and ONL and disruption of EZ, ELM, and IZ.…”
Section: Discussionmentioning
confidence: 99%